Pendidikan Masa Kini Untuk Generasi Penerus Perjuangan Nabi Muhammad SAW. - Mihmidaty Ya’cub (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
To be able to realize the next generation of the Prophet's struggle, professional Islamic teachers are needed, namely teachers who are able to educate their students to become the next generation of the Prophet's struggle. It also requires the ability of teachers to use varied learning methods, productive learning strategies and modern educational media. It is also necessary to provide adequate infrastructure that can support teachers in carrying out the teaching and learning process well and attract students' interest. By knowing the characteristics of this millennial generation, the world of education can play a role and adjust learning strategies in such a way as to bring this millennial generation to an optimal level of success.